Developing Research Skills Across the Undergraduate Curriculum. Issue 169 (March 2015) - Gray, Simon; Coates, Lee; Fraser, Ann; Pierce, Pam
Abstract : This chapter describes consortial efforts within the Great Lakes Colleges Association to share expertise and programming to build research skills throughout the undergraduate curriculum. Strategies to scaffold research skill development are provided from Allegheny College, Kalamazoo College, and The College of Wooster.